A new method for standardization of intraoral radiographs. - (:unkn) unknown (My University, 1996)
Standardization of intraoral radiographs is necessary for longitudinal studies of alveolar bone changes. Several methods of standardizing have been developed. These all involve fixing the geometric relations between the object, the x-ray tube, and the film. This usually involves a film holder, mounted on an occlusal stent and connected to the x-ray tube via an adapter ring. There is, however, a problem of compatibility between various commercial adapter rings and film holder assemblies. In an attempt to overcome this problem, we developed a method of producing cast acrylic adapters by making a plaster cast from a silicon rubber impression of the x-ray tube. The adapter was devised so that radiographs could be taken of all four segments using the same standard commercially available film holder. A total of 128 radiographs were taken from 42 patients who underwent various types of periodontal surgery; 64 were taken preoperatively and 64 at 6 months postoperatively. These pairs were superposed and approximately 58% were found by qualitative inspection to show total matching of geometric outlines as well as maintenance of position on the film, and approximately 73% to show geometric matching. Changes in alveolar bone height were evaluated for 11 of these totally matching pairs by counting millimetric grids and by a computer-based indirect digital imaging system. These were found to correlate satisfactorily (r = .63).